"El mar escupía un lamento". Musical strategies in the face of ecological disasters in contemporary Spain: the cases of the Prestige and the Mar Menor - Fellone, Ugo; Alicia (Cuadernos de Música Iberoamericana, 2025)
This article analyses the musical responses to two marine environmental catastrophes in 21st century Spain: the shipwreck of the oil tanker Prestige near the Galician coast and the Mar Menor crisis in Murcia. Thus, looking at different collective actions, such as songs, concerts, compilations or advertising campaigns, and the way in which they use pre-existing or newly created music, we seek to understand how music is instrumentalized in the struggle for the hegemony of the climate imaginaries defined by Levy and Spicer. To do this, a genealogy of the relationships between music and environmental protest in Spain is drawn, with the aim of understanding what characterizes it and what type of changes have been over time.
Keywords: popular music; protest; climate crisis; climatic disaster; Galicia; Murcia